1998
DOI: 10.1136/bjo.82.9.1033
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Acanthamoeba activity of contact lens solutions

Abstract: Aims-This study was undertaken to investigate the eVects of contact lens disinfecting solutions on strains of Acanthamoeba from the United Kingdom and southern Africa and to compare the results with those of other researchers. No information was previously available for southern African isolates. Methods-11 contact lens solutions were tested on cysts of 10 strains of Acanthamoeba. Results-Not all solutions used in the study were eVective, with some for hard and gas permeable contact lenses being more satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 31 publications
1
41
0
1
Order By: Relevance
“…Our results showing the good cysticidal activity of the two-step system Oxysept 1 correspond to those of other studies and can be explained by the long exposure time to 3% hydrogen peroxide which is not deactivated by a catalytic system (tablet or disk). 20,23 Although the Titmus H 2 O 2 system for disinfection of soft and rigid contact lenses works with hydrogen peroxide at a concentration of only 0.6%, it is more effective than the one-step systems, that contain 3% H 2 O 2 , but in that the neutralisation process starts immediately. This shows clearly, that also with 0.6% H 2 O 2 a complete destruction of Acanthamoeba cysts can be achieved, if this concentration is held up during 8 h and not deactivated by a catalytic system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showing the good cysticidal activity of the two-step system Oxysept 1 correspond to those of other studies and can be explained by the long exposure time to 3% hydrogen peroxide which is not deactivated by a catalytic system (tablet or disk). 20,23 Although the Titmus H 2 O 2 system for disinfection of soft and rigid contact lenses works with hydrogen peroxide at a concentration of only 0.6%, it is more effective than the one-step systems, that contain 3% H 2 O 2 , but in that the neutralisation process starts immediately. This shows clearly, that also with 0.6% H 2 O 2 a complete destruction of Acanthamoeba cysts can be achieved, if this concentration is held up during 8 h and not deactivated by a catalytic system.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the sensitivity of Acanthamoeba cysts against contact lens disinfectants varies between the different strains and morphological groups. 19,23,[27][28] Acanthamoeba cysts are slightly smaller than the trophozoites with a size of 12-28 mm in diameter. They are double-walled consisting of an interior endocyst, which can be stellate, polygonal or even round, and an exterior wrinkled ectocyst.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, fatty acid salts cannot be adsorbed to the cyst wall, and therefore do not show any anti-amoeba activity in cysts. It has been reported that a lower concentration of disinfecting agents results in reduced effect on cysts Tahara et al, 1997;Niszl and Markus, 1998 . In these reports, benzalkonium chloride was shown to be effective against cysts.…”
Section: Fig 4 Acanthamoeba Cells After 60 Min Of Contact With Fattymentioning
confidence: 99%
“…75 The compliance of contact lens users with the recommended care procedures is ineffective if these solutions do not manage to kill Acanthamoeba. 6,105,109 To avoid the persistent use of non-sterile solutions by non-compliant lens wearers, Moore 13 recommended heat disinfection of lenses-between 70 and 80°C for 10 minutes-and the use of 3% hydrogen peroxide for 2-3 hours, 0.001% thimerosal with edetate for 4 hours, 0.005% benzalkonium chloride with edetate for 4 hours, 0.001% chlorhexidine for 4 hours or 0.004% chlorhexidine for 1 hour. Better compliance of contact lens wearers was achieved with the introduction of multipurpose solutions.…”
Section: Non-compliant Contact Lens Usersmentioning
confidence: 99%